An ecological theory of language acquisition - Lacerda, Francisco; Sundberg, Ulla (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
An ecological approach to early language acquisition is presented in this article. The general view is that the ability of language communication must have arisen as an evolutionary adaptation to the representational needs of Homo sapiens and that about the same process is observed in language acquisition, although under different ecological settings. It is argued that the basic principles of human language communication are observed even in non-human species and that it is possible to account for the emergence of an initial linguistic referential function on the basis of general-purpose perceptual, production and memory mechanisms, if there language learner interacts with the ecological environment. A simple computational model of how early language learning may be initiated in today’s human infants is proposed.